Otolith geochemistry in young‐of‐the‐year peacock bass Cichla temensis for investigating natal dispersal in the Rio Negro (Amazon – Brazil) river system. Issue 2 (21st April 2014) - Garcez, Raniere C. S.; Humston, Robert; Harbor, David; Freitas, Carlos E. C.
Abstract: This study examined otolith geochemistry as a natural marker of natal origins in young‐of‐the‐year (YOY) Cichla temensis in the Negro River Basin of Brazil. We analysed trace element and isotopic composition of otoliths of YOY collected off spawning nests from the main stem and major tributaries. These were compared with regional bedrock geologic composition to explore underlying mechanisms of differences in otolith geochemistry. Our results suggest that spatial differences in otolith geochemistry can be used to distinguish natal origins based on 87 Sr/ 86 Sr, Sr/Ca and Ba/Ca ratios. This approach allowed us to correctly classify 99% of juvenile fish to their natal streams using cross‐validation in a linear discriminant function analysis (LDFA). Patterns of otolith isotopic composition correspond with patterns in regional geology as expected based on previously demonstrated correlations, although some fine‐scale spatial differences cannot be accounted for by available geologic information. These results demonstrate that otolith chemistry is valuable as a natural marker of natal origins in this system and suggest that inferences from geologic maps may be useful for interpreting movements based on otolith geochemical signatures. This information provides the basis for future work to investigate the early life history and spatial ecology of this important cichlid.